Urothelial carcinoma of the proximal ureter revealed by spontaneous forniceal rupture: A case report - Moez Rahoui; Hassen Khouni; Rami Boulma (Urology Case Reports, 2022)
Spontaneous rupture of the upper urinary tract is a rare and potentially serious pathology. Lithiasis is the most frequent cause. However, other causes are incriminated such as trauma, retroperitoneal fibrosis and especially stenosing tumors. Few cases of excretory tract rupture secondary to tumor obstruction have been reported in the literature. We report a case of spontaneous rupture of renal pelvis secondary to ureteral obstruction caused by urothelial tumor and discusses difficulties of diagnostic and treatment.